Performance of colloidal CdS sensitized solar cells with ZnO nanorods/nanoparticles - Roy, Anurag; Das, Partha Pratim; Tathavadekar, Mukta; Das, Sumita; Devi, Parukuttyamma Sujatha (Beilstein Journal of Nanotechnology, 2017)
As an alternative photosensitizer in dye-sensitized solar cells, bovine serum albumin (BSA) (a nonhazardous protein) was used in the synthesis of colloidal CdS nanoparticles (NPs). This system has been employed to replace the commonly used N719 dye molecule. Various nanostructured forms of ZnO, namely, nanorod and nanoparticle-based photoanodes, have been sensitized with colloidal CdS NPs to evaluate their effective performance towards quantum dot sensitized solar cells (QDSSCs). A polysulphide (S-x(2-))-based electrolyte and CuxS counter electrode were used for cell fabrication and testing. An interesting improvement in the performance of the device by imposing nanorods as a scattering layer on a particle layer has been observed. As a consequence, a maximum conversion efficiency of 1.06% with an open-circuit voltage (V-OC) of 0.67 V was achieved for the ZnO nanorod/nanoparticle assembled structure. The introduction of ZnO nanorods over the nanoparticle led to a significant enhancement of the overall efficiency compared to the corresponding bare nanoparticles.

Hydrothermally synthesized fluorescent Zn2SnO4 nanoparticles for dye sensitized solar cells - Das, Partha Pratim; Roy, Anurag; Agarkar, Shruti; Devi, Parukuttyamma Sujatha (Dyes and Pigments, 2018)
In this work, we have investigated the interaction of hydrothermally synthesized Zn2SnO4 (ZTO) nanoparticles (NPs) with two different commercial photo sensitizers such as N719 and N3 dye molecules and studied their performance in dye sensitized solar cells (DSSC). Interestingly, the ZTO NPs exhibited band edge emission in the mid UVA region and as a result possibility of enhanced light harvesting in the terminal UVA region was anticipated in the device due to the efficient energy transfer observed in case of the sensitizer N719 than N3. The dye sensitization property has been found to be higher for the N3 dye molecules than the N719 dye molecules as based on the time dependent dye loading study. The devices fabricated with ZTO-N719 exhibited improved photovoltaic performance compared to the ZTO-N3 based devices exhibiting an overall conversion efficiency of 2.56% by the former compared to the later (1.90%) under 1SUN 1.5AM illumination and sensitization for 12 h.